Formulation Development and Evaluation of Self-Microemulsifying Drug Delivery System (SMEDDS) of Azelnidipine for Hypertension - Jukti, Rutik; Kanugo, Abhishek (Indian Journal of Pharmaceutical Education and Research, 2026)
Introduction/Objectives: Azelnidipine is a novel calcium channel blocker usually recommended for the management of an upsurge in blood pressure. The beneficial activity is circumvented because of extreme lipophilicity (Log P: 5.14). The present investigation is dedicated to the expansion of solubility and dissolution of Azelnidipine by self-microemulsifying drug delivery. Materials and Methods: The estimation of solubility of Azelnidipine was checked in several oils, surfactants, and solvents. The inertness of actives with the formulation components was confirmed with FTIR. The pseudo-ternary phase diagram illustrated the microemulsion area. Results: The extreme solubility was noted with oleic acid (oil), Labrasol (surfactant), and PEG 400 (cosolvent). The developed SMEDDS was assessed for globule size, zeta potential, robustness dilution, polydispersity index, viscosity, and in vitro drug release. The best results were displayed by 1:9 oil to Smix ratio with a globule size of 309 nm, zeta potential (-18.3 mV) and PDI (0.377), self-emulsification time (30 sec), drug content (98%) and released within 25 min. The uniformity in globule size and spherical nature was confirmed by Transmission electron microscopy. Conclusion: The results conclude that a mark rise in the solubility, and dissolution rate of Azelnidipine was accomplished with the SMEDDS for their enhanced therapeutic benefits.
Keywords: SMEDDS; Azelnidipine; Hypertension; Microemulsion; Ternary Phase diagram.